2008
DOI: 10.1042/bj20071377
|View full text |Cite
|
Sign up to set email alerts
|

Hepcidin expression in mouse retina and its regulation via lipopolysaccharide/Toll-like receptor-4 pathway independent of Hfe

Abstract: SummaryHepcidin is a hormone central to the regulation of iron homeostasis in the body. It is believed to be produced exclusively by the liver. Ferroportin, an iron exporter, is the receptor for hepcidin. This transporter/receptor is expressed in Müller cells, photoreceptor cells, and retinal pigment epithelium (RPE) within the retina. Since the retina is protected by the retinal-blood barriers, we asked whether ferroportin in the retina is regulated by hepcidin in the circulation or whether the retina produce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
74
1
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(77 citation statements)
references
References 46 publications
0
74
1
2
Order By: Relevance
“…A recent study found that Hep is expressed in M ü ller cells, photoreceptor cells, and retinal pigmented epithelium. The expression of Hep in the retina points to the local intraocular regulation of iron metabolism, separate from a dependence on the circulation liver-derived hormone: circulating Hep would likely be inaccessible to intraocular tissues due to the presence of blood-ocular barriers (99) . Recently, it was shown that local Hep secretions may have a pathogenic role in POAG (100) , however, the authors raised a number of questions that need to be elucidated before fi nal conclusions are drawn.…”
Section: Hepcidinmentioning
confidence: 99%
“…A recent study found that Hep is expressed in M ü ller cells, photoreceptor cells, and retinal pigmented epithelium. The expression of Hep in the retina points to the local intraocular regulation of iron metabolism, separate from a dependence on the circulation liver-derived hormone: circulating Hep would likely be inaccessible to intraocular tissues due to the presence of blood-ocular barriers (99) . Recently, it was shown that local Hep secretions may have a pathogenic role in POAG (100) , however, the authors raised a number of questions that need to be elucidated before fi nal conclusions are drawn.…”
Section: Hepcidinmentioning
confidence: 99%
“…32 Animals were weighed and anesthetized using 17 lL (1 lL/g body weight) of a solution of ketamine (80 mg/mL) and xylazine (12 mg/mL). Then 5 lL of proparacaine solution (5% w/v) was administered topically to the eyes.…”
Section: Intravitreal Injection Of Mmfmentioning
confidence: 99%
“…8,9 Moreover, the absence or low expression of hepcidin is implicated in the etiology of hereditary hemochromatosis as a primary cause of iron overload 10 whereas its over-expression has been linked to iron deficiency anemia. 11 While a number of cell types are known to express hepcidin, [12][13][14][15][16] serum hepcidin levels are mainly determined by production and release of the peptide by hepatocytes; however, the involvement of other cell types in the regulation of hepatocyte hepcidin is unclear. Macrophages are primary candidates for such a role as they provide the majority of serum iron recycled from senescent erythrocytes and are also intrinsically involved in innate immunity and awakening of the adaptive immune response.…”
Section: Introductionmentioning
confidence: 99%